ANALISIS STRATEGI PEMASARAN GO-JEK INDONESIA PASCA KELUARNYA UBER DARI PASAR TRANSPORTASI DARING INDONESIA (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2018)
This study aims to analyze the empirical evidence of Go-Jek Indonesia's marketing strategy after the exit of the market from the Indonesian online transportation market. The development of the online motorcycle taxi market is very dynamic, in 2018 Uber left Indonesia and was acquired by Grab. After this event, Go-jek needs a revaluation of its marketing strategy to capture the opportunity to move consumers from Uber and strengthen its position as the ruler of the online motorcycle taxi market in Indonesia. The main finding of this research is that Go-jek is expected to conduct revaluation on the segmentation and positioning of the Go-jek brand in the market. The expansion of segmentation is needed to capture first-class consumer opportunities and increase brand awareness. Go-jek can use the promo code marketing strategy in its application to increase the opportunity to purchase services again. The development of features that accept credit cards as payments can also be an effective marketing strategy to capture Uber consumers. Research recommends Go-jek to develop credit card features, Go-jek Premium with high-capacity vehicles, promotion at events with top-class economic segmentation and expansion of marketing strategies in the aggregate.